Country attributes on the adoption of the IFRS for SMEs - Natário, Marisa Marques (2022)
Small and Medium-sized Entities (SMEs) are crucial in the global economy and the urge to develop a standard for these companies rapidly arose. The International Accounting Standards Board (IASB) contribution began in 2009 with the issuing of the International Financial Reporting Standard for SMEs (IFRS for SMEs). The IFRS for SMEs adoption is a decision that is up to each country to make. However, little is known about the reasons that drive countries to require, to permit or to prohibit the standard. This dissertation investigates 120 countries worldwide during 2018 and 2019 and aims to study the influence of multiple competitiveness attributes of each country to understand the reasons of a country may i) require, ii) permit, iii) prohibit but use similar standards or iv) prohibit and use different standards. A multinomial logistic regression was conducted revealing that overall, countries that have a higher competitiveness level in institutions, health, skills, product market and financial system are more likely to require the IFRS for SMEs. Meanwhile, countries more competitive in infrastructures, Information and Communications Technology (ICT) adoption, macroeconomic stability, business dynamism and innovation capability are more likely to not require the IFRS for SMEs. Understanding and recognizing the attributes that distinguish a country where the IFRS for SMEs is required from one where it is permitted or prohibited may be important to governments, accounting standards setters, and regulators.